PERLINDUNGAN HUKUM TERHADAP LANJUT USIA TERLANTAR DI KABUPATEN TORAJA UTARA (Fakultas Hukum Univesitas Kristen Indonesia Paulus, 2023)
Humans as creatures of God Almighty were created in His image and likeness so that they are said to be the most noble creatures. Humans in addition to having a relationship with God, also have a relationship with other humans, so that humans cannot live alone. This study aims to determine the legal protection of neglected elderly and to know the role of social services in handling cases of neglected elderly. This study uses research methods conducted by field research (Field Research) conducted at the Toraja Utara Social Service Office. This research is qualitative, where the types of data used are primary and secondary data. The results of this study indicate that neglected elderly victims are entitled to protection from the police, social workers, social worker services, companion volunteers, and also neglected elderly have rights and obligations that must be fulfilled both physically and spiritually where the role of the Social Service is needed to handle cases These are the facilitative role, the educational role, the representational role and the technical role.